FINANCIAL STATE AND SOLVENCY MONITORING AS THE MOST SIGNIFICANT INSTRUMENT FOR DIAGNOSTICS HUI ENTERPRISE ACTIVITIES - S. E. Kovan (Real Economics Publishing House, 2015)
The issue of rising functional efficiency and assuring solvency of HUI organizations is discussed. Systematic analysis and financial state assessment, as well as monitoring these organizations constitute an important instrument in making timely managing decisions and preventing their insolvency. The article states main tasks and principles of conducting utility enterprise monitoring.